SYSTEMATIC LITERATURE REVIEW: ANALISIS PERBANDINGAN TAX AMNESTY ANTARNEGARA - Windi Satria Ananda (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This study aims to analyze the factors driving the success and the challenges of tax amnesty policies in various countries, with a focus on Indonesia. Using the systematic literature review (SLR) method, this research finds that the success of tax amnesty is influenced by effective promotion, low tax rates, tax reforms, and strong law enforcement. Failure is caused by policy repetition, weak law enforcement, and perceptions of unfairness among taxpayers. In Indonesia, although tax amnesty programs I and II have shown positive results, the targets for fund repatriation and tax compliance have not been achieved. Recommendations for Indonesia include strengthening law enforcement, tax reforms, and improving public information transparency. This study provides guidance for enhancing the effectiveness of future tax amnesty programs.